NORMS AND NEW MEDIA AS NEW PILLARS OF NEW NETWORK TERRORISM - Ahmad Saifuddin (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2022)
Terrorism is a constant phenomenon. However, the pattern and style of terrorism have changed considerably since 2010. This paper uses a case-study approach to explore the factors that lead individuals to join terrorist groups today. Analysts have long focused on three factors that drove individuals to join terrorist groups: